Domestic electrical appliances consumption: the case of Centre of Foundation Studies for Agricultural Science UPM students - Baderus, Amirul Hakimi; Mohamed Isa, Siti Suzilliana Putri; Mohamad Nazir, Aina Suhaiza; Zainol Jamil, Noor Wahidah; Abdul Aziz, Nor Azah; Omar Baki, Sharudin; Mohd Tarmizi, Emma Ziezie; Mohd Noor, Ikhwan Syafiq; Mansor, Yaakob; Zainol Abidin, Nadiah Husseini (2019)
The electrical consumption for domestic applications in Peninsular Malaysia is investigated in this paper. The study is performed among the homes of Physics students at Centre of Foundation Studies for Agricultural Science, Universiti Putra Malaysia (UPM). The approximately 500 homes in Peninsular Malaysia are selected in this study, where the electricity in this region is governed by Tenaga Nasional Berhad (TNB). The purpose of this study is to recognize the electrical usage for the various types of household electrical appliances, together with their cost which contribute to the amount of electric bill. As a result, this study will be able to determine which household appliances consumes the most energy and cost. Thus, the paper also includes several practical ways to conserve electricity.